2015
DOI: 10.1007/s00134-015-3899-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticosteroids for sepsis: systematic review with meta-analysis and trial sequential analysis

Abstract: Introduction Glucocorticosteroids (steroids) are widely used for sepsis patients. However, the potential benefits and harms of both high and low dose steroids remain unclear. A systematic review of randomised clinical trials with meta-analysis and trial sequential analysis (TSA) might shed light on this clinically important question.MethodsA systematic review was conducted according to a published protocol and The Cochrane Handbook methodology including meta-analyses, TSA of randomised clinical trials, and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 57 publications
1
90
0
2
Order By: Relevance
“…In a systemic review and meta-analysis which was done in 2015, a total of 35 articles were assessed. It included 4682 patients and there was no relation between steroid doses and mortality (24). Death in patients with and without diabetes had a significant difference.…”
Section: Discussionmentioning
confidence: 98%
“…In a systemic review and meta-analysis which was done in 2015, a total of 35 articles were assessed. It included 4682 patients and there was no relation between steroid doses and mortality (24). Death in patients with and without diabetes had a significant difference.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, TSA suggested that many more randomized patients are needed to draw a conclusion. 43 Although in the CORTICUS trial shock reversal with the LDCs was achieved quickly, there was increased evidence of new sepsis or septic shock in the hydrocortisone group (OR 1.37, p<0.05). 32 They also showed increased rates of hyperglycemia and hypernatremia in the treatment group.…”
Section: Systematic Review and Meta-analyses Conducted On The Use Of mentioning
confidence: 99%
“…There have been previous meta-analyses of steroids within the critical care environment [2][3][4], but, to our knowledge, this is the first using an NMA approach and the first analysis focussing on the effect of the therapeutic agent and regimen. Although all corticosteroids possess the immune, metabolic and fluid homeostatic features of their group, marked differences in the activity of each drug in these features exists.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Second, do steroids given to all critically ill patients improve outcomes [2]? These questions have been investigated primarily in those patients with septic shock, and sufficient studies have been conducted to allow multiple meta-analyses [2][3][4], including a recently updated Cochrane review [2]. However, not all therapeutic corticosteroids are the same.…”
Section: Introductionmentioning
confidence: 99%